COMPARISON OF EFFECTS OF EXTRACT OF MYRISTICA FRAGRANS AND VERAPAMIL ON THE VOLUME AND ACIDITY OF CARBACHOL INDUCED GASTRIC SECRETION IN FASTING RABBITS - Jan, Muhammad; Faqir, Farah; Mughal, Muhammad Azhar (Journal of Ayub Medical College Abbottabad, 2005)
Background: Peptic ulcer is mostly produced due to the over production of gastric acid. This study was undertaken to find out the effects of extract from Myristica Fragrans which contains documented natural Calcium channel blocker and Verapamil on volume and acidity of Carbacol induced gastric section. Their effects were also compared to find out any difference in their efficacy. Methods: Thirty rabbits of local breed, weighing 1-1.5kg were used. The animals were kept on fasting for 48 hours, after which the pylorus of each animal was ligated. Verapamil 10mg/kg, Myristica fragrans 500 mg/kg and Carbachol 600mg/kg body weight were administered intraperitoneally. Results: It was found that extract from Myristica fragrans reduced the volume, free and total acidity of gastric secretion, which were statistically highly significant when compared with Carbachol (P<0.001). Verapamil had also the same effects. When the difference of mean for verapamil was compared with that of extract, all these differences were found statistically non significant indicating that extract has similar effect as that of Verapamil on all parameters included in study. Conclusion: The effect of Myristica Fragrans is similar to Verapamil and therefore it can be used effectively in the treatment of peptic ulcer and all other conditions that require calcium channel blockers for the treatment of these disorders. Keywords: Myristica Fragrans, Verapamil, gastric acid secretion, Medicinal plant